Entry deterrence through cooperative R&D over-investment - Clémence Christin (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
In this paper, we highlight new conditions under which R&D agreements may have anti-competitive effects. We focus on cases where two firms compete with each other and with a competitive fringe. R&D activities need a specific input available to all firms on a common market, the price of which increases with demand for the input. In such a context, if a firm increases its R&D expenses, it increases the cost of R&D for its rivals. This induces exit from the fringe and may increase the final price. Therefore, by contrast to the case where the cost of R&D for one firm is independent of its rivals' R&D decisions, cooperation between strategic firms on the upstream market may induce more R&D by strategic firms, in order to exclude firms from the fringe and increase the final price.
Keywords: L13; L24; L41; 330; Competition policy; Research and Development Agreements; Collusion; Entry deterrence